Evaluation of Erytra® fully automated analyser for Routine Use in Transfusion Laboratory. Issue 1 (5th November 2013) - Chang, C.; Brown, M.; Davies, L.; Pointon, L.; Brown, R.; Barker, D.
SUMMARY Objective To evaluate efficiency and performance of Erytra® analyser in comparison to the reference platform of the NBT immunohaematology laboratory (Bio‐Rad ID‐System). Background Moving to automation or semi‐automation is a major focus of transfusion centres. The Erytra® (Grifols) is a new fully automated walk‐away analyser with high volume processing capacity for pre‐transfusion testing, designed to be used with the unique 8‐column DG Gel® cards. Study Design and Methods A total of 2201 immunohaematological tests (1041 ABO/D grouping, 1041 antibody screening, 51 antibody identification, 45 newborns (ABO/D and DAT) and 23 crossmatches were performed on 1160 donor/patient whole blood samples. Erytra®'s performance was assessed by means of a stress test replicating the routine work of a hospital laboratory. Results Concordant results between the Erytra® and the reference method were obtained in 2195 (99·73 %) of the tests. There were only three discrepancies out of 6246 reactions (0·05%) in ABO/D grouping, all in the reverse group which did not mislead to group identification. Of the 1041 samples screened for antibody presence, Erytra® detected all the relevant antibodies [9 not detected weak prophylactic anti‐D were determined to be clinically nonsignificant (<0·1 IU mL−1)] while Bio‐Rad ID‐System missed one anti‐e and one anti‐Jka. Concordance for D grouping, crossmatching and newborns was 100%. Results of the simulated stress test exercise highlighted the capacity of Erytra® for absorbing into 4 h workloads equivalent to 24 h of routine. Conclusions Grifols' Erytra® analyser showed reliable high sensitivity, velocity and capacity to cope with high workload in the immunohaematology laboratory routine.